Development of chromogenic detection for biomolecular analysis. Issue 1 (31st January 2022) - Peng, Weipan; Li, Wenna; Han, Houyu; Liu, Hao; Liu, Ping; Gong, Xiaoqun; Chang, Jin
Abstract: Chromogenic detection of target objects has attracted extensive attention in the academic field with high specificity and sensitivity. Based on color changes in chemical reactions, biomolecular analysis with simple and rapid signal readout in disease diagnosis can be realized. At present, three main mechanisms of chromogenic detection were proposed, including proteases catalysis, enzyme mimics catalysis, and chemical reactions based on inorganic or organic for biomolecular analysis. With the unremitting efforts of scientific researchers, the evolution of chromogenic detection has been developed from the early qualitative detection to the current quantitative detection, accompanied by the improvement of sensitivity. Herein, this paper reviewed the mechanisms and relevant applications of chromogenic detection from the above three aspects, discussed the challenge, and provided a future perspective in this emerging field. Abstract : Chromogenic detection of target objects has attracted extensive attention in the academic field with high specificity and sensitivity. Bimolecular analysis with simple and rapid signal readout in disease diagnosis can be realized based on color changes in chemical reactions. At present, three main mechanisms of chromogenic detection were proposed, including proteases catalysis, enzyme mimics catalysis, and chemical reactions based on inorganic or organic for biomolecular analysis. Herein, this paper reviewed the mechanisms and relevant applications of chromogenic detection from the above three aspects, discussed the challenge, and provided a future perspective in this emerging field.